Manifestations of Irrational Thinking in Neurotic Disorders - Abitov, I (KnE Life Sciences, 2018)
The study addresses peculi arities of irrational thinking in neurotic disorders. Some scholars (V. N. Myasischev, V. D. Mendelevich, A. I. Zakharov, B. J. Zebb, M. C. Moore, C. Sica, C. Novara, E. Sanavio, B. Futrell, P. Brugger, I. Viaud-Delmon, S. N. Enikolopov and S. V. Lebedev) indicate that there exists a relationship between neurotic symptoms and irrational thinking. To reveal the peculiarities of irrational thinking we used the following methodology: The Paranormal Belief Scale ( J. Tobacyk, adapted by D. S. Grigoriev), the Superstitiousness Inventory (I. Abitov) and the Constructive Thinking Inventory (S. Epstein, adapted by S. N. Enikolopov and S. V. Lebedev). The population of the study consisted of 50 patients undergoing in-patient neurotic disorders treatment at the psychotherapeutic department of the Kazan’ city clinical hospital No. 18. Control group included 50 respondents who did not have neurotic disorders in their medical stories and had not previously sought psychotherapeutic aid. The acquired data show that neurotic disorders patients are more inclined to believe in psychic abilities (like psychokinesis or levitation) and to observe various superstitious beliefs. Also, it was revealed that neurotic disorders patients have higher indexes of behavioral coping than the control group, that is, they tend to undertake particular actions to solve problems. In addition to the aforementioned, they have higher results of the scales ‘Superstitious Thinking’ and ‘Naive Optimism’. Correlational analysis showed that the neurosis patients’ group has inverse correlations between Constructive thinking on the one hand and Superstitiousness and Witchcraft belief on the other hand. The research findings correspond with the results gained by S. N. Enikolopov and S. V. Lebedev and may be used in indicating the so-called ‘psychotherapeutic targets’ and in planning the psychotherapeutic intervention. Keywords: irrational thinking, superstitiousness, paranormal beliefs, constructive thinking, neurotic disorders